Excerpts from the author’s works - Stefanovsky, Voria (Romano džaniben, 2021)
Czech translation of three poems by V. Stefanovsky (Enought!; Everyday Oddysey; The day I can´t forget) and one short story (Between you and me and the bedpost) all dealing with the topic of gender, with the author´s foreword about her life and the story of her road to writing.